2016
DOI: 10.1038/srep39493
|View full text |Cite|
|
Sign up to set email alerts
|

Gene expression differences in Longissimus muscle of Nelore steers genetically divergent for residual feed intake

Abstract: Residual feed intake (RFI), a measure of feed efficiency (FE), is defined as the difference between the observed and the predictable feed intake considering size and growth of the animal. It is extremely important to beef production systems due to its impact on the allocation of land areas to alternative agricultural production, animal methane emissions, food demand and cost of production. Global differential gene expression analysis between high and low RFI groups (HRFI and LRFI: less and more efficient, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 60 publications
7
66
0
2
Order By: Relevance
“…Collectively, these results point out that scd1a expression contributes to mitigate the signs of n-3 LC-PUFA deficiencies, but at the same time, that it is very important to limit its up-regulation to avoid the dysregulation of hepatic metabolism and the lipotoxic effects of excessive fat accumulation. In agreement with this notion, targeted disruption of the mice Scd1 gene reduced body adiposity and provide resistance to diet-induced weight gain [77], as well as reduced fat accumulation in liver [33], and among livestock, lower SCD1 expression have been associated with fed efficiency and lean growth in cattle [78]. However, the relationship between SCD1 expression and fat accumulation in humans remains controversial, as vary between obese and lean subjects [79], and between carbohydrate-rich [73] and high-fat diets [80].…”
Section: Phenotypic Outputs Of Fish Scd1a Programmingmentioning
confidence: 67%
“…Collectively, these results point out that scd1a expression contributes to mitigate the signs of n-3 LC-PUFA deficiencies, but at the same time, that it is very important to limit its up-regulation to avoid the dysregulation of hepatic metabolism and the lipotoxic effects of excessive fat accumulation. In agreement with this notion, targeted disruption of the mice Scd1 gene reduced body adiposity and provide resistance to diet-induced weight gain [77], as well as reduced fat accumulation in liver [33], and among livestock, lower SCD1 expression have been associated with fed efficiency and lean growth in cattle [78]. However, the relationship between SCD1 expression and fat accumulation in humans remains controversial, as vary between obese and lean subjects [79], and between carbohydrate-rich [73] and high-fat diets [80].…”
Section: Phenotypic Outputs Of Fish Scd1a Programmingmentioning
confidence: 67%
“…Oxidative stress reprograms lipid metabolism increasing the mitochondrial fatty acid oxidation 31 . Butanoate metabolism was also found to be enriched for differentially expressed genes in Nelore cattle muscle for RFI 32 . In our study, we found acetoacetate as the hub metabolite responsible for butanoate metabolism related to TDG in Duroc TP2 ( Supplementary Table S3).…”
Section: Discussionmentioning
confidence: 93%
“…A specific example of this includes the UQCRQ gene, which was identified as differentially expressed in the muscle tissue from these animals and displayed the same direction of expression in all cohorts [5]. Oxidative stress has been proposed in many other studies as a factor that affects feed efficiency in swine, poultry, and beef cattle [25][26][27][28][29][30].…”
Section: Genes/pathways Identified For Gainmentioning
confidence: 95%